COVID 19- STRESS MANAGEMENT AMONG STUDENTS AND ITS IMPACT ON HIGHER EDUCATION - Mrs. Licy Varghese (Galaxy International Interdisciplinary Research Journal, 2022)
The academic competition among the students has created a lot of stress among the students that adversely affects their academic performance. Stresses among the students have become a common phenomenon due to rapid increment in the cut-throat competition. In the present time, various things put the students under stress such as achieving good marks in their academics as well as they face pressure from their parents, family, and society. It is important to properly manage the stress otherwise it will destroy the future of the students. Academic stress is one of the most common stresses found among students of higher education. Academic stress leads the students into depression and causes anxiety, frustration and sometimes it leads to suicide. In this article, we will discuss the method through which the stress can be managed among the students as well as their consequences on the performance of the students.